2010
DOI: 10.1007/s10658-010-9595-z
|View full text |Cite
|
Sign up to set email alerts
|

Verticillium wilt of olive in Turkey: a survey on disease importance, pathogen diversity and susceptibility of relevant olive cultivars

Abstract: A comprehensive survey on the prevalence and incidence of Verticillium wilt of olive in Turkey has been conducted over 6 years (2003)(2004)(2005)(2006)(2007)(2008). Vegetative compatibility group (VCG) assessment and PCR-based molecular pathotyping were used to evaluate the distribution of the defoliating (D) and nondefoliating (ND) pathotypes of Verticillium dahliae in surveyed areas. Pathogen prevalence was 35% of all olive orchards inspected and incidence of the disease reached 3.1%. VCG1A was predominant (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
45
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 49 publications
(51 citation statements)
references
References 28 publications
1
45
0
Order By: Relevance
“…Similarly, it induces reduction in weight and, to a lesser extent, in height under favorable environmental conditions (López-Escudero and Blanco-López 2001;López-Escudero et al 2004, 2007aMartos-Moreno et al 2006). Differences in virulence seem to be consistent among olive cultivars (López-Escudero et al 2004, 2007aMartos-Moreno et al 2006;Dervis et al 2010). The broad host range and apparent low host specificity suggests that V. dahliae populations contain low pathogenic and genetic diversity.…”
Section: Pathogenicity Groupsmentioning
confidence: 89%
See 4 more Smart Citations
“…Similarly, it induces reduction in weight and, to a lesser extent, in height under favorable environmental conditions (López-Escudero and Blanco-López 2001;López-Escudero et al 2004, 2007aMartos-Moreno et al 2006). Differences in virulence seem to be consistent among olive cultivars (López-Escudero et al 2004, 2007aMartos-Moreno et al 2006;Dervis et al 2010). The broad host range and apparent low host specificity suggests that V. dahliae populations contain low pathogenic and genetic diversity.…”
Section: Pathogenicity Groupsmentioning
confidence: 89%
“…A survey in the Apulia region (Southern Italy) revealed that 16% of surveyed olive fields were infested with V. dahliae, and, more importantly, the pathogen was found in 50% of olive nurseries analyzed (Nigro et al 2005). Finally, a recent inspection covering 90% of the total olive acreage in Turkey revealed that V. dahliae was prevalent in 35% of all olive orchards inspected and that DI reached 3.1% (Dervis et al 2010). Reports are also confirming the presence of the disease in non traditional olive cultivating countries such as Australia (Sergeeva and Spooner-Hart 2009) or Argentina .…”
Section: Current Importance Of Verticillium Wilt Of Olivementioning
confidence: 96%
See 3 more Smart Citations